Distinguishing between slip and twinning events during nanoindentation of magnesium alloy AZ31. (1st January 2016) - Guo, Tingting; Siska, Filip; Barnett, M.R.
Graphical abstract: During the penetration of a spherical indenter, the pop-in events can be observed on the load–penetration depth curves. Catoor et al. (2013) have found the 〈a〉 type dislocations and extension twins in TEM by probing the 3.3 μm radius spherical indenter on single crystal Mg. However, in their research, they did not find when the extension twin appeared. So at present work, we solved this problem by probing a 5 μm radius indenter on selected grains of polycrystal Mg alloy AZ31. Multiple indentation tests were performed on a large [ 1 1 2 ¯ 0 ] oriented grain, and two curves with same applied load of 1.5 mN and their residual imprint are displaying in the pictogram. Curve (a) shows "yielding" event, and it is found that the basal slip is the only deformation mode observed in the AFM image. While both "yielding" and "pop-in" events are observed on curve (b). Inspection of its AFM image reveal the presence of the basal slip lines and the extension twin on the surface of the indent. This confirms that the initial yielding behavior is due to slip and subsequent pop-in is due to the onset of a twinning event. Abstract: Nanoindentation was performed in selected grain orientations close to [ 1 1 2 ¯ 0 ] and [ 1 0 1 ¯ 0 ] in magnesium alloy Mg–3Al–1Zn. The atomic force microscopy (AFM) and electron backscatter diffraction (EBSD) were used to examine the nanoindentation imprint. Two critical events, yielding and pop-in were observed in the depth–load curves. Slip trace analysis suggests that basal slip is responsible for yielding. The following pop-in events at higher loads are associated with the appearance 1 0 1 ¯ 2 twins on the surface. The critical resolved shear stress (CRSS) was estimated to be in the range of 220–400 MPa for the initiation of basal slip.